Cyclopia maculata : source of flavanone glycosides as precursors for taste modulating aglycones - Du Preez, Brigitte Von Pressentin (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScFoodSc)--Stellenbosch University, 2014.